Analysis of the Factors that Influence Demand for Broiler meat in the City of Gunungsitoli - Zandroto, Yansen (Jurnal Peternakan Integratif, 2021)
Consumption of chicken meat is very accepted by consumers compare to other kind of meat. The purpose of the study was to find out the factors that influence the demand for broiler chicken meat in Gunungsitoli city. The research was conducted from May until June 2021 using primary data. The method used in sampling is interviewing respondents with purpossive sampling (intentionally) and in analysis with Multiple Linear Regression using SPSS 24 application tool. The results showed that the demand for broiler chicken meat in Gunungsitoli city was influenced simultaneously by the price of broiler chicken meat, age, number of family members, income level, fish price, taste level, and education level with RÂ²=0.606. The price of broiler chicken meat, income level and taste level have a noticeable effect on the confidence level of 95%.